Faktor-Faktor Yang Berhubungan Dengan Kejadian COVID-19 Di Desa Naru, Kecamatan Woha, Kabupaten Bima, Provinsi Nusa Tenggara Barat - Rini Aryanti; Agus Setyobudi; Deviarbi Sakke Tira (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
The case of the spread of the Covid-19 virus in Woha District, Bima Regency, West Nusa Tenggara experienced an increase in the number of Covid-19 cases, the most of which were 19 cases in Naru Village. The cause of the high number of cases in Naru Village is due to its location close to the city. Other factors that have contributed to the Covid- 19 incident are knowledge, attitudes, Covid-19 prevention measures, the availability of facilities and family support that have a relationship with the Covid-19 incident. This study aims to analyze the factors related to the incidence of Covid-19 in Naru Village, Woha District, Bima Regency, West Nusa Tenggara Province in 2021. This type of research is an analytical survey with a cross sectional study approach design. The population is all the heads of families in Naru Village, finding 255 family heads. The sampling technique used simple proportional sampling with a sample of 70 families. The data obtained were then analyzed using chi square with a significance level = 0.05. The results showed that there was a relationship between the three variables with the incidence of covid-19, namely preventive measures (p = 0.044), availability of facilities (p = 0.040) and family support (p = 0.020). In addition, there are two variables that do not have a relationship, namely knowledge (p = 0.832) and attitude with a value of (p = 0.771). It is hoped that the people of Naru Village will get information from various trusted sources, especially healthworkers, television and social media related to the Covid-19 incident